СЕМЕЙНЫЕ НАБЛЮДЕНИЯ СИНДРОМА НУНАН: КАРДИОЛОГИЧЕСКИЙ СТАТУС ПАЦИЕНТОВ ПРИ ПАТОГЕННЫХ ВАРИАНТАХ В ГЕНЕ PTPN11 - Румянцева, Наталья Владимировна; Зобикова, Ольга Леонидовна; Голубева, Светлана Владимировна (FORCIPE, 2022)